Enhanced strength and durability of long fiber type carbon fiber reinforced plastic rods over titanium alloy rods for spinal fixation - Kohei Morita, MD, PhD; Hiroki Ohashi, MD, PhD; Katsuhiro Oikawa; Satoshi Tani, MD, PhD; Kostadin Karagiozov, MD, PhD; Yuichi Murayama, MD (North American Spine Society Journal, 2025)
Background: Carbon fiber-reinforced plastic (CFRP) has been used in many medical devices, including rods for posterior spinal fixation devices, owing to its superior radiolucency and durability compared with titanium alloys. However, the strength of the existing short fiber type CFRP does not surpass that of metals. Recently, the use of innovative technologies for manufacturing long fiber type CFRP has dramatically improved their strength. In this study, we developed a rod for posterior spinal fixation using long fiber type CFRP technology and evaluated its strength, durability, and radiolucency against rods made of titanium alloy, cobalt chrome, short fiber CFRP, and polyaryletherketone (PEEK). Methods: Comparison tests were conducted on the strength, durability, and image evaluation of long fiber type CFRP rods and titanium alloy rods. In addition, a series of tests required for regulatory approval and clinical use were conducted. Results: The long fiber type CFRP rod showed 120% of the strength of the titanium alloy rod, 102% of that of the cobalt chrome rod, and approximately 20 times the strength of the short fiber type CFRP and PEEK, demonstrating durability that remarkably exceeded that of the titanium alloy. Moreover, artifacts in the radiographic images were smaller than those observed with titanium alloy. Biosafety and magnetic resonance safety tests also yielded satisfactory results, supporting approval for clinical use. Conclusion: This study introduces a new type of long fiber type CFRP rod for spinal surgery that is stronger, lasts longer, and causes fewer imaging problems than current titanium rods, and may prevent complications such as rod breakage. The long fiber type CFRP rod may improve the safety and outcomes of spinal surgeries.